DESCRIPTION OF CHARACTERISTICS OF CHRONIC ENERGY DEFICIENCY (CED) IN PREGNANT WOMEN IN KAWAY XVI DISTRICT, ACEH BARAT REGENCY - Mohd Haikal; Susy Sriwahyuni; Arfah Husna (RADJA PUBLIKA, 2022)
Nutrition is one of the main determinants of the quality of human resources. Chronic Energy Deficiency (CED) is one of the four main nutritional problems in Indonesia. Chronic Energy Deficiency (CED) and anemia have a greater risk of illness, especially in the third trimester of pregnancy compared to normal pregnant women. As a result, pregnant women have a greater risk of giving birth to babies with low birth weight, death during childbirth, bleeding, difficult delivery because they are weak and easy to experience health problems. This research uses a survey method with a descriptive approach . The research was carried out in Kaway XVI District, Aceh Barat Regency spread over 4 villages, namely Keude Tanjung Village, Puuk Village, Tanjong Bungong Village and Pungkie Village, from August 7 to December 15, 2021. The population in this study was CED pregnant women as many as 21 people. The results showed that there were more respondents in the status of not working as many as 18 people (85.7%), Mothers who had never had children as many as 11 people (52.4%), Mothers who consumed 15 people (71.4%). , good ANC as many as 15 people (71.4%), income < UMP as many as 19 people (90.5%), age group 20-35 years as many as 16 people (76.2%) and no history of CED as many as 15 people (71.4%).